Decision Support System Using the TOPSIS Method in New Teacher Selection - Hts, Dedek Indra Gunawan; Desi, Efani; Aliyah, Siti; Nasution, Fitri Pranita; Indriani, Ulfah; Edi, Firman (Politeknik Ganesha Medan, 2024)
Every school needs teachers who have good competence to educate students to become outstanding students. Getting teachers who have good competence is certainly not an easy thing, it must be a very strict selection process. This research aims to help determine teachers who are eligible to be accepted at IT Al Munadi Private Elementary School Medan by using the TOPSIS method. The selection consists of 5 criteria, namely education, microteaching, teaching experience, tahsin and memorization of the Koran. The TOPSIS method is widely used for Multi Attribute Decision Making (MADM) decision making. The TOPSIS method is used as a ranking to see teachers who have competencies that are worthy of acceptance. Based on the results of the TOPSIS calculation where there are 6 alternatives that have been determined, the results obtained are G6 in the first place with a preference value of 2.82, 2nd place with a preference value of 2.48, 3rd place with a preference value of 2.09, 4th place with a preference value of 1.72, 5th place with a preference value of 1.67, while the 6th place is G1 with a preference value of 1.00. It is hoped that the decision support system using TOPSIS can help schools in determining teachers who have good competence so as to produce outstanding students.